In-vitro antibacterial activity and phytochemical screening of bioactive compounds from guava (Psidium guajava L.) crude leaf extracts - Shafiei, Siti Nur Sarah (2012)
Plant pathogenic bacteria are known to be detrimental microbes able to reduce the quality and quantity of crop production around the world. Psidium guajava leaf was screened for its potential use as biological control agent against plant pathogenic bacteria. P. guajava leaf was successfully extracted using n-hexane, ethyl acetate and methanol by maceration. The yield percentage of crude extracts obtained for each extract was 0.93% for hexane, 1.28% for ethyl acetate and 1.70% for methanol leaf crude extracts. The higher yield obtained by methanol showed that methanol extracted more compounds that are readily soluble to methanol than hexane and ethyl acetate. For in vitro antibacterial activity, seven different species of plant pathogenic bacteria were used namely Pectobacterium carotovorum subsp. carotovorum, Pectobacterium chrysanthemi, Ralstonia solanacearum, Xanthomonas axonopodis pv. citri, Xanthomonas euvesicatoria, Xanthomonas oryzae pv. oryzae and Xanthomonas oryzae pv. oryzicola. For all crude extracts, four different concentrations 25, 50, 100 and 200 mg/ml were used in cup-plate agar diffusion method. Streptomycin sulfate at concentration of 30 μg/ml was used as positive control, while each respective solvent used for leaf extraction was used as negative control. The results obtained from in vitro studies showed only methanol extract possessed antibacterial activity tested on the plant pathogenic bacteria. Hexane and ethyl acetate did not show any antibacterial activity against plant pathogenic bacteria where no inhibition zones were recorded. X. oryzae pv. oryzae recorded the highest diameter of inhibition zones for all range of concentrations introduced followed by X. oryzae pv. oryzicola, X. euvesicatoria, X. axonopodis pv. citri, P. chrysanthemi and P. carotovorum subsp. carotovorum. For minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) determination, only methanol extract was subjected for the assay as only methanol extract exhibited antibacterial activity. The lowest concentration of methanol extract used in MIC assay was at 0.39 mg/ml which inhibited X. oryzae pv. oryzae, followed by X. euvesicatoria (0.78 mg/ml), and X. oryzae pv. oryzicola, X. axonopodis pv. citri, P. chrysanthemi and P. carotovorum subsp. carotovorum at concentration 1.56 mg/ml. This assay showed that methanol extract had bacteriostatic effects at concentration 0.39, 0.78 and 1.56 mg/ml for different species of plant pathogenic bacteria. The lowest MBC concentration recorded was at 0.78 mg/ml against X. oryzae pv. oryzae, 1.56 mg/ml against X. euvesicatoria, 3.13 mg/ml against X. oryzae pv. oryzicola and X. axonopodis pv. citri, and 6.25 mg/ml against P. chrysanthemi and P. carotovorum subsp. carotovorum. The phytochemical screening of P. guajava methanol leaf extracts showed the presence of alkaloids, flavonoids, tannins, saponins, terpenoids and phenols. The thin layer chromatography (TLC) profiling of methanol extract using hexane and ethyl acetate with ratio of 7:3 (v/v) gave 13 maximum colorful bands when visualized with 10% ethanolic sulfuric acid solution, with different retention factor, Rf values which proved the presence of various active secondary metabolites within methanol extract. The antibacterial activity of methanol extract was also screened through direct bioautography technique in order to detect the location of active bands on hromatograms developed in the same matter for TLC profiling. The most active Rf values which inhibited all tested plant pathogenic bacteria at the same Rf values location were at 0.63, 0.85, and 0.98. The Rf values obtained were compared to the previous studies performed using the same solvent system indicated that the Rf values recorded at >0.90 belongs to hydrocarbons, and 0.60-0.80 belongs to epoxides and esters which were found to fall within oxygenated terpenes group.